Gender Relation in Willow Trees Don’t Weep Novel (2014) by Fadia Faqir: A Feminist Literary Criticism - Ida Rosida; Aini Soraya (Insaniyat : Journal of Islam and Humanities, 2017)
This  study  is  aimed  at  finding  gender  relations  between  male  and  female  character  as  they  are depicted  in  Willow  Trees  Don’t  ’Weep  (2014)  novel  written  by  Fadia  Faqir.  This  study  employs descriptive qualitative method on feminist literary criticism as a theory to find and reveal gender issues. The text is analyzed by using feminist criticism “woman as reader” to give the evaluation and  interpretation  on  how  woman  writes  about  woman.  The  result  shows  that  there  are  three significant points in which gender relation in patriarchal culture is portrayed in the novel. They are male  domination,  discrimination  towards  women,  and  violence  against  women.  The  results  were evaluated  by  examining  female  character’s  condition  in  a  patriarchal  society  through  woman’s point of view based on her social life and experiences. Moreover, the country where women live is influenced the gender relation. Jordan in this case, has the strongest patriarchal system compared to Pakistan, Afghanistan, and London (the countries where Najwa lived while searching for her father).DOI: 10.15408/insaniyat.v2i1.6586